Coronavirus Disease 2019 Hangover: A Rising Tide of Alcohol Use Disorder and Alcohol‐Associated Liver Disease. Issue 3 (28th September 2020) - Da, Ben L.; Im, Gene Y.; Schiano, Thomas D.
Abstract : The coronavirus disease 2019 (COVID‐19) pandemic has had a tremendous global impact since it began in November of 2019. However, there are concerns that the COVID‐19 pandemic will not affect all equally and that some populations will be particularly vulnerable. Relevant to liver disease, patients with alcohol use disorder (AUD) and alcohol‐associated liver disease (ALD) may be among the populations that are the most severely impacted. The reasons for this include being at a higher risk of severe COVID‐19 infection due to a depressed immune system and high‐risk underlying comorbidities, the injurious effect of COVID‐19 on the liver, the inability to attend regular visits with providers, diversion of hospital resources, and social isolation leading to psychological decompensation and increased drinking or relapse. As a result, we fear that there will be a dramatic rising tide of alcohol relapse, admissions for decompensated ALD, and an increase in newly diagnosed patients with AUD/ALD post–COVID‐19 pandemic. Providers and their institutions should implement preemptive strategies such as telehealth and aggressive patient outreach programs now to curb this anticipated problem. Liver transplantation (LT) centers should adapt to the pandemic by considering leniency to some LT candidates with ALD who cannot access appropriate alcohol treatment due to the current situation. In conclusion, the COVID‐19 pandemic will likely be especially detrimental to patients with AUD/ALD, and actions need to be taken now to limit the scope of this anticipated problem.